2020
DOI: 10.1111/nyas.14456
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the assessment and management of pharyngoesophageal dysphagia

Abstract: Swallowing complaints are common and may have significant consequences for nutrition and pulmonary health. Etiology varies and different aspects of the deglutitive system may be affected. A thorough assessment from the oral cavity to the stomach will provide physiologic information that enables specific targeted management plans to be devised. Although the swallow trajectory bridges anatomic areas, there has previously been a tendency to compartmentalize assessment and treatment by arbitrary anatomic boundarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…First, this study has developed an educational program based on the idea that professional development is necessary to enable high-quality dysphagia management. It has been reported that long-term treatment outcomes of dysphagia can be optimized when a multidisciplinary team provides comprehensive management for each patient on an individual basis (Allen et al, 2020). In Japan, the revision of the medical fee system for fiscal year 2020 established an additional fee for swallowing support under medical planning and support for patients with dysphagia by the feeding support team.…”
mentioning
confidence: 99%
“…First, this study has developed an educational program based on the idea that professional development is necessary to enable high-quality dysphagia management. It has been reported that long-term treatment outcomes of dysphagia can be optimized when a multidisciplinary team provides comprehensive management for each patient on an individual basis (Allen et al, 2020). In Japan, the revision of the medical fee system for fiscal year 2020 established an additional fee for swallowing support under medical planning and support for patients with dysphagia by the feeding support team.…”
mentioning
confidence: 99%